(untitled) (Indonesian Economic Justice Review, 2024)
This paper explores the rise of the gig economy in Indonesia and its implications for economic justice, particularly concerning labor rights and protections for gig workers. The gig economy, characterized by short-term contracts, freelance work, and platform-based employment, has expanded rapidly in Indonesia, driven by technological advancements and the increasing demand for flexible work arrangements. However, the growth of the gig economy raises concerns about job insecurity, lack of social protections, and unequal access to benefits for workers. This paper investigates the legal and policy frameworks governing gig work in Indonesia, focusing on labor laws, social security provisions, and the role of digital platforms in shaping working conditions. Through qualitative interviews with gig workers, including ride-hailing drivers, delivery personnel, and online freelancers, the paper examines the challenges they face in terms of income stability, health insurance, and retirement benefits. The findings suggest that gig workers often experience exploitation due to the absence of formal labor protections and weak enforcement of existing regulations. The paper concludes with recommendations for policymakers to better regulate the gig economy, ensuring fair wages, worker protections, and access to social benefits, while balancing the needs of businesses and workers in an increasingly digital economy.